Block compost for acid mine drainage remediation and as a growing medium for Melaleuca cajuputi seedlings - Daniswati, Nisa; Mansur, Irdika; Herliyana, Elis Nina (Brawijaya University, 2026)
Environmental problems arising from mining include the formation of acid mine drainage (AMD), which contains high levels of heavy metals and has a low pH, requiring remediation. Block compost made from goat manure and mushroom baglog waste has the potential to remediate AMD and serve as a planting medium. The objectives of this study were to analyze the effect of block compost on AMD remediation and to assess its effect as a planting medium on the growth of Melaleuca cajuputi. This study used a completely randomized design with six block compost composition treatments: without block compost (P0), mushroom baglog waste 70% + cement 30% (P1), goat manure 70% + cement 30% (P2), goat manure 35% + mushroom baglog waste 35% + cement 30% (P3), goat manure 25% + mushroom baglog waste 45% + cement 30% (P4), goat manure 45% + mushroom baglog waste 25% + cement 30% (P5). The results showed that the treatment of block compost with various compositions (P1, P2, P3, P4, P5) was effective in increasing the pH of AMD from 3 to 5.1-6.4 and reducing the concentration of Cd, Cu, Pb, and Zn metals by 45.74-82.70% within 5 days. The application of block compost with various compositions also had a significant effect on the height growth of Melaleuca cajuputi. The P3 treatment significantly increased the height of the seedlings to 34.00 cm within 8 weeks.